Urban tomographies - Krieger, Martin H. (City in the twenty-first century book series., 2011)
Like a CAT scan of an organ, urban tomography documents metropolitan life by sampling and compiling multiple slices of a city. Using photography and audio recording, urban planning expert Martin H. Krieger scans contemporary Los Angeles to illuminate different aspects of a community, from work to worship.